Dietary and Behavioral Risk Factors of Ischemic Heart Disease Among Patients of Medical Outpatient Departments in Southern Ethiopia: Unmatched Case-Control Study - Gebremedhin MH; Gebrekirstos LG (Dove Medical Press, 2021)
Meron Hadis Gebremedhin,1 Lielt Gebreselassie Gebrekirstos2 1School of medicine, College of health science and medicine, Wolaita Sodo University, Wolaita Sodo, Ethiopia; 2Department of maternity and reproductive health, College of health science and medicine, Wolaita Sodo University, Wolaita Sodo, EthiopiaCorrespondence: Meron Hadis Gebremedhin Tel +251 9-1639-7836Email merykiyaggg@gmail.comBackground: Worldwide mortality due to cardiovascular disease is the dominant cause of death, and ischemic heart disease is the leading one. Though risk factors for Ischemic heart diseases are modifiable and preventable, it is not well investigated in the local context. Thus, this study aimed to assess the dietary and behavioral risk factors for ischemic heart disease among patients in medical outpatient departments in Southern, Ethiopia.Methods: A facility-based unmatched case-control study was conducted from November 16 to March 20, 2020, among patients with ischemic heart disease and those patients who visited the three hospitals of the Wolaita Zone. A convenient sampling method was used and the data were entered using Epi data version 3.1 and exported to SPSS version 21 for analysis, a p-value < 0.05, were considered statistically significant.Results: A total of 557 study participants (140 cases and 417 controls) were included in a ratio of 1:3. The adjusted odds ratio for having no formal education (AOR = 3.18; 95% CI: 1.59, 6.34), previous history of hypertension (AOR= 2.84; 95% CI: 1.73, 4.66), physical inactivity (AOR= 2.23; 95% CI: 1.32, 3.76), inadequate intake of fruit and vegetable consumption (AOR= 2.43; 95% CI; 1.40, 4,22), palm oil use for food preparation (AOR= 2.12; 95% CI: 1.23, 3.63) and obesity (AOR= 5.68; 95% CI: 2.63, 12.23) increased the occurrence of the disease.Conclusion: Although ischemic heart disease is preventable, using relatively simple and inexpensive lifestyle changes, it is projected to cause preventable loss of life. So, expanding health education and healthy life styles including exercise is recommended.Keywords: behavioral, ischemic heart disease, case-control, logistic regression, Ethiopia